Utilization of Instagrams as a Medium of Self-Existence on Lettering Arts Activities - Mohammad Insan Romadhan; Muchamad Rizqi; Ajeng Ferdiawati (2021)
This study examines the existence of lettering artists by utilizing Instagram social media. The authors are interested in examining Nur Awaludin’s image because Nur Awaludin’s track record and works which can be found in several places. In addition, not many people know about lettering artists although they enjoy the work they make. The theory used in this study is the impression management theory from Erving Goffman. The method used in this study is descriptive qualitative data collection technique through the results of in-depth interview with informants, observations, and documentation study through social media Instagram. The results showed that Nur Awaludin used Instagram and its features. Nur Awaludin also showed good impressions and was in accordance with the image that was built as a lettering artist by following the Subletter community and by creating a team project called Kid Project.